Labor market regulations and cross-border mergers and acquisitions - Alimov, Azizjon (Journal of International Business Studies, 2015)
This article exploits changes in country-level employment protection regulations as a source of plausibly exogenous variation in labor laws and finds that these regulations play an important role in cross‐border merger activity. Over the 1991–2009 period, countries that tighten employment regulations attract more foreign acquirers, especially those from countries with relatively more flexible labor regulations. The results appear to be robust to alternative specifications. Importantly these patterns are pronounced in those recipient country sectors in which foreign acquirers may find attractive targets at bargain prices: sectors with relatively high productivity and skill. The article also provides evidence suggesting that, because pro-labor reforms allow foreign acquirers to cherry pick more skilled and productive local firms, these transactions are associated with greater deal synergies and improved post-merger operating performance.